A lot sizing model for imperfect and deteriorating product with destructive testing and inspection errors. Issue 1 (2nd January 2021) - Sharifi, Ebrahim; Hasanpour, Javad; Taleizadeh, Ata Allah
ABSTRACT: Nowadays, the management and control of perishable inventories is important in many units and industrial enterprises. Perishable inventory management and control is more complex and challenging than inventories with unlimited lifetime. Hence determining the optimal inventory policies for these products is very important. In this paper, the optimal inventory policy for perishable products, produced in a system that manufactures prefect and imperfect items, using a sampling plan for accepting incoming lot is developed. The test used to ensure the quality of products is destructive and there are inspection errors. After developing a model for the problem and obtaining the objective function, first a simple algorithm is proposed to calculate the optimal order quantity. Then, the proposed model is validated using numerical examples after which sensitivity analysis is performed.